Inverse definite overcurrent relay discrimination algorithm and its application in industrial power systems - Noor Zaihah, Jamal; Omar, Aliman; M. H., Sulaiman (Asian Research Publishing Network (ARPN), 2015)
In a normal electrical network, it is crucial to design a system complete with protection to prevent any abnormalities or fault occurrence to disturb the whole source of electrical to be shut down. Only a portion of effected area should be closed and fault duration at high current value should be closely monitored. Overcurrent protection device discrimination play vital roles to ensure protective relay will react accordingly. This paper introduces a systematic overcurrent discrimination algorithm which is based on standard formulationand constant value by IEC 60255-4 and IEEE Std C37.112-1996. The proposed algorithm has been tested to an 11k V industrial power system. Two bus data have been tested and the tests result of the network was studied, analyzed and discussed. The algorithm has proven successfully fulfilled the discrimination requirement.